Anil Kumar-Singh (Farmer), Jamnapur, Bihar India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Anil Kumar-Sing is an Indian farmer with a family to provide for. He talks about the consequences of the decreasing water level and how the lack of an electrical infrastructure does not allow them to use water pumps and to irrigate the fields. The changing weather is really becoming a problem.